PEMANFAATAN MALTODEKSTRIN DARI PATI SINGKONG SEBAGAI BAHAN PENYALUT LAPIS TIPIS TABLET - Anwar, Effionora (UI Scholars Hub, 2002)
The Use of Maltodextrin from Tapioca Starch as a Film Coating Tablet Material. Maltodexrin is a modifi ed starch product which can be use as a material fi lm coating tablet. The aim of the research was to study the capability of maltodextrin as a material fi lm coating exipient. Maltodextrin DE 5-10 was made by hidrolysis of tapioca starch with α-amylase enzyme from NOVO (Termamyl L120®), at 80° C, for 65 minute. Maltodextrin was used as a fi lm coating material at concentration 10%,15%,20% dan 25%. As a comparative fi lm coating material was used HPMC. The evaluation of the coating tablet was done accordance to Farmacope Indonesia third and fourth edition. The result show that maltodextrin DE 5-10 from tapioca starch can be used as fi lm coating at concentration 10-25% with concentration 10% gave better result a HPMC